Pengaruh Kepuasan Kerja Dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior Pada PT. Pegadaian Cabang Tenggarong - Iskandar Iskandar; Agustina Liana (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Abstract: The purpose of this study was to determine the effect of Organizational Commitment and Job Satisfaction on Organizational Citizenship Behavior at PT. Pegadaian (Persero) Cabang Tenggarong either partially or simultaneously. Respondents in this study were drawn from all employees of PT. Pegadaian Tenggarong Branch, totaling 25 employees. The analytical tool used is a Multiple Regression model. The results of the calculation of the F test (simultaneous), the variable Job Satisfaction and Organizational Commitment simultaneously affect the Organizational Citizenship Behavior. Job Satisfaction (X1) and Organizational Commitment variable has a positive influence on Organizational Citizenship Behavior. From the two partial correlation test results above, it can be seen that the value of the Big Five Personality (X1) variable is the largest compared to with the organizational commitment variable (X2), so the Big Five Personality (X1) variable is the biggest, the dominant variable affecting the Organizational Citizenship Behavior of PT. Pegadaian (Persero) Branch of Tenggarong. Keywords: Big Five Personality, Organizational Commitment, Organizational Citizenship Behavior